The Impacts of Globalization on Human Resource Development Management - Ali Gunawan; Stephen Gregorius Kurnia; Hasan Ghazali (Social Economics and Ecology International Journal (SEEIJ), 2019)
The terms “Globalization” and “The Digital Era” are familiar words that sound in our ears which mean progress or development.  The term globalization is a term that has links to increase interdependence among nations and people around the world through trade, investment, travel, popular culture and other forms of interaction so that the boundaries of a country become biased.  Globalization can bring about changes in all areas such as culture, economy, social, politics, ideology and so on.  On the one hand, globalization brings with its positive consequences and on the other hand also carries negative sides.  The Digital Era supports the process of Globalization to make it easier to accomplish, which makes it all easy to communicate with anyone and anytime, accessing data and information easily and quickly wherever we are especially supported by the tools of modern softwares and hardwares.  The Digital Era can also develop the capabilities of human resources must be able to adjust to use it.  For human resources who are unable to compete will be replaced with more capable ones.  However, currently Human Resources in Indonesia have not been fully encouraged to enter the Digital Era due to the constraints of several factors, such as the availability of infrastructure, the cost of digital is still inadequate when associated with the number of people with the level education and low technological understanding so they are accustomed to do jobs that do not require special skills.  Here ther role of all groups, communities and governments, to further improve the skills of human resources so as to be able to improve the economy and welfare.